2002
DOI: 10.1002/1521-4141(200207)32:7<1883::aid-immu1888>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

The follicular dendritic cell restricted epitope, FDC-M2, is complement C4; localization of immune complexes in mouse tissues

Abstract: We have identified the murine follicular dendritic cell (FDC) marker, FDC‐M2, recognized by monoclonal antibody mAb209, as complement component C4. Consistent with this, FDC‐M2 was detectable at sites of immune complex‐mediated inflammatory disease. Analysis of FDC‐M2 distribution in complement‐deficient mice highlighted the differences in immune complex clearance between these mice, andshowed that a population of uncharacterized FDC‐M2+ reticular and perivascular cells in the spleen, distinct from FDC, are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 26 publications
4
50
0
Order By: Relevance
“…Although this statement may appear a contradiction, it is experimentally validated: in 2003, Rahman et al (23) showed that all splenic GCs of SRBC-immunized A/J and C57BL/6 mice stain extensively for Ki-67. In agreement with FDC-M2 is a well-established and widely used FDC marker that is also lowly expressed on white pulp reticular cells and some uncharacterized perivascular cells (37). However, the latter does not interfere with detection of FDC networks or other GC cell populations.…”
Section: Identification Of Gcssupporting
confidence: 63%
“…Although this statement may appear a contradiction, it is experimentally validated: in 2003, Rahman et al (23) showed that all splenic GCs of SRBC-immunized A/J and C57BL/6 mice stain extensively for Ki-67. In agreement with FDC-M2 is a well-established and widely used FDC marker that is also lowly expressed on white pulp reticular cells and some uncharacterized perivascular cells (37). However, the latter does not interfere with detection of FDC networks or other GC cell populations.…”
Section: Identification Of Gcssupporting
confidence: 63%
“…Recent studies have identified the antigen recognized by the FDC-specific antiserum FDC-M2 as complement component C4 (55). Thus, the temporary loss of FDC-M2-specific immunostaining after treatment with LT␤R-Ig is also consistent with the inability of these cells to trap and retain complementopsonized antigens.…”
mentioning
confidence: 86%
“…Control conditions included B cells alone, B cells plus anti-IgD mAb, B cells plus anti-IgD ICs, and B cells plus antiIgD mAb plus FDCs. FDC-M2 is a rat anti-mouse mAb that detects an epitope of C4 localized to the ICs trapped on FDCs (21,32). This anti-C4 appears to block C4-BP, which is capable of interacting with CD40 on B cells (21).…”
Section: Assessment Of Fdc-baff Production and The Effect Of Neutralimentioning
confidence: 99%